Efficacy of Herbicides on Weed Suppression and Yield Performance of Onion (Journal of the Bangladesh Agricultural University, 2026)
Weed management is one of the significant challenges of vegetable tuber crops since weeds pose a remarkable threat to crop productivity in Bangladesh. A field experiment on efficacy of different herbicides for controlling weeds in onion field was conducted during the rabi season of 2024-25 at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Cumilla, Bangladesh. The treatments included pendimethalin 33% EC @ 800 ml ha-1 (T1) applied at the 2–4 leaf stage of weeds, pendimethalin 33% EC @ 1000 ml ha-1 (T2) spraying on soil 1-2 days before transplanting, oxyfluorfen 23.5% EC @ 750 ml ha-1 (T3) spraying at 3-4 day before transplanting, atrazine 50% + mesotrione 5% SC @ 1000 ml ha-1 (T4) &  @ 1500 ml ha-1 (T5) spraying at 3-4 day before transplanting, two hand weeding at 25 and 50 days after transplanting (T6) and  a control (T7) with three replications. Results revealed significant differences among treatments in terms of weed dry weight, seedling mortality, bulb yield and economic returns. Atrazine 50% + mesotrione 5% SC @ 1500 ml ha-1 (T5) provided the highest weed control efficacy (up to 91%). Pendimethalin, hand weeding and control recorded 0% mortality of onion seedling. Pendimethalin was effective in controlling both broad leaf and narrow leaf weeds. Maximum bulb yield (18.25 t ha-1), the highest gross return (5,47,410 Tk. ha-1) and highest benefit–cost ratio (2.77) was obtained from pendimethalin 33% EC @ 1000 ml ha-1 (T2). In contrast, atrazine and mesotrione based combinations (T4 and T5) caused severe phytotoxicity with seedling mortality exceeding 75%, resulting in low yield (5.94–6.50 t ha-1), negative gross margins and poor BCR values (